Conductive film and method for producing the same
By inserting transition element ions between layers of MXene material, a MXene film containing transition elements is formed, which solves the problem of conductivity stability of MXene material under hygroscopic conditions, and achieves high initial conductivity and hygroscopic resistance.
Patent Information
- Application Number
- CN202280009193.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2021-01-13
- Filing Date
- 2022-01-04
- Publication Date
- 2025-03-07
- Estimated Expiration
- 2042-01-04
AI Technical Summary
The prior art is difficult to achieve high initial conductivity and stable conductivity in MXene materials, especially under hygroscopic conditions.
The MXene film containing the transition element is formed by inserting transition element ions, such as ions of Ti, V, Cr, Zr, Nb, Mo, Hf, Ta, W and Y, between layers of the MXene material. The method of manufacturing the film includes preparing a precursor film having a specific layered structure and coating a solution containing transition element ions on its surface.
The high initial conductivity and stability of MXene material is achieved, and it can maintain more than 10% of the conductivity under high humidity environments, which significantly improves the material's hygroscopic resistance and strength.
Smart Images

Figure CN116745864B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a conductive film and a method for producing the same. Background Art
[0002] In recent years, MXene has attracted attention as a new material with electrical conductivity. MXene is a so-called two-dimensional material, and as described later, is a layered material having one or more layers. Generally speaking, MXene has the form of particles of such layered materials (also called MXene particles, which may include powder, flakes, nanosheets, etc.).
[0003] Currently, various studies are being conducted on the application of MXene in various electrical devices. For the above applications, it is required to improve the conductivity, strength and other properties of materials containing MXene. As part of the research, attempts are made to insert metal ions into MXene. For example, Patent Document 1 proposes to make the surface and interlayer of MXene powder contain metal nanoparticles such as nano-nickel particles, nano-copper particles, nano-aluminum particles, and nano-magnesium particles, so as to improve the strength of MXene.
[0004] Furthermore, Non-Patent Document 1 describes that Li cations are present in the interlayer gaps of MXene due to LiCl used in chemical etching, and that the structure of the powder changes by exchanging the Li cations with other metal ions.
[0005] Prior art literature
[0006] Patent Literature
[0007] Patent Document 1: Chinese Patent Application Publication No. 109207834
[0008] Non-patent literature
[0009] Non-patent literature 1: Michael Ghidiu et al., "Ion-Exchange and Cation Solvation Reactions in Ti3C2 MXene", Chemistry of Materials, 2016, Volume 28, pp. 3507-3514 Summary of the invention
[0010] Problems to be solved by the invention
[0011] New materials having electrical conductivity are required to have high initial electrical conductivity and to suppress the time-dependent deterioration of electrical conductivity due to moisture absorption, that is, to exhibit stable electrical conductivity, but Patent Document 1 and Non-Patent Document 1 do not disclose any improvement in these characteristics. The present invention has been made in view of the above circumstances, and its object is to provide a conductive film having high initial electrical conductivity and exhibiting stable electrical conductivity, and a method for producing the same.
[0012] Means of solving the problem
[0013] According to one aspect of the present invention, there is provided a conductive film comprising particles of a layered material having one or more layers, wherein:
[0014] The layer comprises: a layer of the following formula: M m X n a layer body represented by (wherein, M is at least one metal of Groups 3, 4, 5, 6, and 7, X is a carbon atom, a nitrogen atom, or a combination thereof, n is greater than 1 and less than 4, and m is greater than n and less than 5); a modification or terminal T present on the surface of the layer body (T is at least one selected from the group consisting of a hydroxyl group, a fluorine atom, a chlorine atom, an oxygen atom, and a hydrogen atom),
[0015] The conductive film contains one or more transition elements selected from the group consisting of Ti, V, Cr, Zr, Nb, Mo, Hf, Ta, W and Y.
[0016] According to another aspect of the present invention, there is provided a method for manufacturing a conductive film, comprising:
[0017] (a1) preparing a precursor film, the precursor film comprising a layered material particle having one or more layers, the layer comprising: m X n A layer body represented by (wherein, M is at least one metal of Groups 3, 4, 5, 6, and 7, X is a carbon atom, a nitrogen atom, or a combination thereof, n is 1 to 4, and m is greater than n and 5 or less); a modification or terminal T present on the surface of the layer body (T is at least one selected from the group consisting of a hydroxyl group, a fluorine atom, a chlorine atom, an oxygen atom, and a hydrogen atom); and
[0018] (b1) A solution is applied on the precursor film, wherein the solution contains, as ions in a solvent, one or more transition elements selected from the group consisting of Ti, V, Cr, Zr, Nb, Mo, Hf, Ta, W and Y.
[0019] Effects of the Invention
[0020] According to the present invention, a conductive film is formed of a prescribed layered material (also referred to as "MXene" in this specification) and contains one or more transition elements selected from the group consisting of Ti, V, Cr, Zr, Nb, Mo, Hf, Ta, W and Y, thereby providing a conductive film containing MXene, having high initial conductivity and excellent conductivity stability.
[0021] In addition, according to the present invention, the conductive film can be manufactured by (a1) preparing a predetermined precursor film; and (b1) coating the precursor film with a solution containing as ions one or more transition elements selected from the group consisting of Ti, V, Cr, Zr, Nb, Mo, Hf, Ta, W and Y in a solvent. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 The diagrams are schematic cross-sectional views showing MXene, a layered material that can be used in a conductive film according to an embodiment of the present invention. (a) shows a single-layer MXene, and (b) shows a multi-layer (two-layer, for example) MXene.
[0023] Figure 2 The diagrams schematically illustrate the mechanism by which the conductive film of the present invention exhibits adsorption resistance, wherein (a) shows a conventional MXene film without a transition element, and (b) shows a MXene film (conductive film) containing a transition element.
[0024] Figure 3 This is a diagram illustrating the interlayer distance of the transition element-containing MXene particles of the present invention.
[0025] Figure 4 This is a schematic diagram for explaining one example of an external mixing multi-fluid nozzle that can be used to produce a precursor film in the production method of the present invention.
[0026] Figure 5 This is a schematic diagram for explaining another example of an external mixing multi-fluid nozzle that can be used to produce a precursor film in the production method of the present invention.
[0027] Figure 6 This is a graph showing the change in conductivity over time in Examples.
[0028] Figure 7 The following are photographs showing the results of the first tape peeling test of the examples. (a) is a photograph of Example 1, (b) is a photograph of Comparative Example 1, and (c) is a photograph of Comparative Example 2.
[0029] Figure 8 The following are photographs showing the results of the second tape peeling test of the examples. (a) is a photograph of Example 1, (b) is a photograph of Comparative Example 1, and (c) is a photograph of Comparative Example 2.
[0030] Fig. 9 This is a diagram showing the XRD results of the sprayed MXene film of the example.
[0031] Fig.10 It means to enlarge Fig. 9 Figure 3. XRD results of a portion (low angle side) of the sprayed MXene film.
[0032] Fig.11 It means to enlarge Fig. 9 Figure 2 is a graph of the XRD results of the sprayed MXene film on another part (high angle side).
[0033] Fig.12 This is a diagram showing the XRD results of another sprayed MXene film of the example. DETAILED DESCRIPTION
[0034] (Embodiment 1: Conductive Film)
[0035] Hereinafter, a conductive film according to one embodiment of the present invention will be described in detail, but the present invention is not limited to this embodiment.
[0036] The conductive film of this embodiment is a conductive film including particles of a layered material having one or more layers.
[0037] The layers include:
[0038] By the following formula: M m X n a layer body represented by (wherein, M is at least one metal of Groups 3, 4, 5, 6, and 7, X is a carbon atom, a nitrogen atom, or a combination thereof, n is greater than 1 and less than 4, and m is greater than n and less than 5); a modification or terminal T present on the surface of the layer body (T is at least one selected from the group consisting of a hydroxyl group, a fluorine atom, a chlorine atom, an oxygen atom, and a hydrogen atom),
[0039] The conductive film contains one or more transition elements selected from the group consisting of Ti, V, Cr, Zr, Nb, Mo, Hf, Ta, W and Y.
[0040] In this specification, in order to distinguish the conductive film of this embodiment from the MXene film not containing the above transition elements, it is sometimes referred to as a "transition element-containing MXene film" or a "transition element ion-loaded MXene film". In addition, in the manufacturing method of this embodiment, the MXene film not containing the above transition elements is referred to as a "precursor film". In addition, the layered material constituting the precursor film is referred to as "MXene", its particles are referred to as "MXene particles", and the particles of the layered material constituting the conductive film of this embodiment are referred to as "transition element-containing MXene particles".
[0041] The above-mentioned layered materials can be understood as layered compounds, also expressed as "M m X n T s ", s is an arbitrary number. Historically, x or z is sometimes used instead of s. Typically, n can be 1, 2, 3 or 4, but is not limited thereto.
[0042] In the above formula of MXene, M is preferably at least one selected from the group consisting of Ti, Zr, Hf, V, Nb, Ta, Cr, Mo and Mn, and more preferably at least one selected from the group consisting of Ti, V, Cr and Mo.
[0043] In MXene, it can be seen that the above formula: M m X n The expression is as follows.
[0044] Sc2C, Ti2C, Ti2N, Zr2C, Zr2N, Hf2C, Hf2N, V2C, V2N, Nb2C, Ta2C, Cr2C, Cr2N, Mo2C, Mo 1.3 C.Cr 1.3 C, (Ti, V)2C, (Ti, Nb)2C, W2C, W 1.3 C, Mo2N, Nb 1.3 C.Mo 1.3 Y 0.6 C (In the above formula, "1.3" and "0.6" mean approximately 1.3 (= 4 / 3) and approximately 0.6 (= 2 / 3), respectively.)
[0045] Ti3 C2, Ti3N2, Ti3(CN), Zr3 C2, (Ti, V)3C2, (Ti2Nb)C2, (Ti2Ta)C2, (Ti2Mn)C2, Hf3 C2, (Hf2V)C2, (Hf2Mn)C2, (V2Ti)C2, (Cr2Ti)C2, (Cr2V)C2, (Cr2Nb)C2, (Cr2Ta)C2, (Mo2 Sc)C2, (Mo2Ti)C2, (Mo2Zr)C2, (Mo2Hf)C2, (Mo2V)C2, (Mo2Nb)C2, (Mo2Ta)C2, (W2Ti)C2, (W2Zr)C2, (W2Hf)C2,
[0046] Ti4N3, V4C3, Nb4C3, Ta4C3, (Ti, Nb)4C3, (Nb, Zr)4C3, (Ti2Nb2)C3, (Ti2Ta2)C3, (V2Ti2)C3, (V2Nb2)C3, (V2Ta2)C3, (Nb2Ta2)C3, (Cr2Ti2)C3, (Cr2V 2)C3, (Cr2Nb2)C3, (Cr2Ta2)C3, (Mo2Ti2)C3, (Mo2Zr2)C3, (Mo2Hf2)C3, (Mo2V2)C3, (Mo2Nb2)C3, (Mo2Ta2)C3, (W2Ti2)C3, (W2Zr2)C3, (W2Hf2)C3, (Mo 2.7 V 1.3 )C3 (In the above formula, "2.7" and "1.3" mean about 2.7 (= 8 / 3) and about 1.3 (= 4 / 3), respectively.)
[0047] Typically, in the above formula, M can be titanium or vanadium, and X can be a carbon atom or a nitrogen atom. For example, MAX phase is Ti3AlC2, and MXene is Ti3C2T s (In other words, M is Ti, X is C, n is 2, and m is 3).
[0048] In addition, in the present invention, MXene may contain a relatively small amount of residual A atoms, for example, 10% by mass or less relative to the original A atoms. The residual amount of A atoms may preferably be 8% by mass or less, and more preferably 6% by mass or less. However, even if the residual amount of A atoms is higher than 10% by mass, there may be no problem depending on the purpose and use conditions of the conductive film.
[0049] The transition element-containing MXene particles of this embodiment contain transition elements, and the interlayer distance of the layered material is enlarged, etc., and the structure equivalent to the skeleton is the same as that of the MXene particles constituting the precursor film. The structure equivalent to the skeleton of the transition element-containing MXene particles is described below. Figure 1 Transition elements are not shown.
[0050] The above MXene particles contain Figure 1 The MXene 10a (single-layer MXene) is schematically shown as an aggregate of one layer. More specifically, MXene 10a is a MXene having m X n The layer body represented by m X n The MXene layer 7a is a MXene layer having a modified or terminal portion T3a or 5a on the surface of the main layer 1a (more specifically, at least one of the two surfaces of each layer facing each other). Therefore, the MXene layer 7a is also represented as “MXene layer 7a”.m X n T s ", s is an arbitrary number.
[0051] The above MXene particles may include one layer and multiple layers. As multiple layers of MXene (multilayer MXene), such as Figure 1 (b) schematically shows that two layers of MXene 10b can be listed, but the present invention is not limited to these examples. Figure 1 1b, 3b, 5b, 7b in (b) are the same as those mentioned above. Figure 1 (a) 1a, 3a, 5a, 7a are the same. Two adjacent MXene layers (e.g., 7a and 7b) of the multilayer MXene are not necessarily completely separated, but may be partially in contact. The MXene10a is that the multilayer MXene10b is separated individually and exists as one layer, or it may be a mixture of the single-layer MXene10a and the multilayer MXene10b that remains without separation.
[0052] Although not limiting the present embodiment, the thickness of each layer of MXene (corresponding to the above-mentioned MXene layers 7a and 7b) is, for example, 0.8 nm to 5 nm, particularly 0.8 nm to 3 nm (mainly depending on the number of M atomic layers contained in each layer). In each stack of multilayer MXene that can be contained, the interlayer distance (or gap size, in Figure 1 The thickness of the layer (represented by Δd in (b)) is, for example, 0.8 nm to 10 nm, particularly 0.8 nm to 5 nm, more particularly about 1 nm, and the total number of layers may be 2 to 20,000.
[0053] The above-mentioned MXene particles are preferably the above-mentioned multilayer MXene, which is a MXene with a small number of layers obtained by interlayer exfoliation treatment. The "small number of layers" refers to, for example, that the number of layers of the MXene is 6 or less. In addition, the thickness of the multilayer MXene with a small number of layers in the stacking direction is preferably 10nm or less. Hereinafter, this "multilayer MXene with a small number of layers" is referred to as "few-layer MXene". In addition, single-layer MXene and few-layer MXene are collectively referred to as "single-layer·few-layer MXene".
[0054] The MXene particles preferably include monolayer MXene and few-layer MXene, i.e., monolayer·few-layer MXene. In the conductive film of this embodiment, the proportion of monolayer·few-layer MXene with a thickness of 10 nm or less is 50% by volume or more, further 70% by volume or more, further 90% by volume or more, and further 95% by volume or more.
[0055] The conductive film of the present embodiment contains one or more transition elements selected from the group consisting of Ti, V, Cr, Zr, Nb, Mo, Hf, Ta, W and Y. It is known that MXene interacts with the d orbital of the metal, but the electrons of the d orbital of these transition elements interact easily with the π electrons of MXene, and it is easy to ensure the effect of maintaining the layers and layers of MXene, so it is believed that it helps to improve the stability of the conductivity. In addition, by playing the role of maintaining the layers and layers of MXene, it also helps to improve the strength of the conductive film. The above-mentioned transition elements may be the same as or different from the elements constituting MXene. The conductive film of the present embodiment preferably carries ions of the above-mentioned transition elements on MXene. That is, the transition element-containing MXene particles are preferably transition element-carrying MXene particles. In this specification, the so-called "carrying" refers to the state in which the above-mentioned transition elements do not constitute MXene itself, and the ions of the transition metal or the inorganic acid salt of the transition metal are present between the layers of MXene. The inorganic acid salt, for example, is an inorganic acid salt that can be used in step (b1) or step (d2) of the method for manufacturing the conductive film. For example, if the inorganic acid salt is titanium sulfate, titanium ions can be present between layers of MXene in a state where the titanium ions are bonded to sulfate ions as counter ions.
[0056] The difference between the bond between the transition metal ion and the counter ion in the inorganic acid salt and the bond between the transition metal and carbon and nitrogen in the carbide and nitride of the transition metal that is considered to be mixed as an impurity can be confirmed by XPS (X-ray photoelectron spectroscopy). In addition, the presence of the above transition elements between MXene sheets can be confirmed by TEM (transmission electron microscopy), for example.
[0057] Among the above transition elements, one or more of Ti, Cr and Y are preferred, and Ti is most preferred.
[0058] The transition element is preferably present between the layers. When the transition element is, for example, Ti, Figure 2 (b) Schematic illustration, it is believed that transition elements, especially ions ( Figure 2 In the case of the above, Ti ions 41 are inserted into the interlayers of the transition element MXene particles 10d, and Ti ions 41 are carried between the interlayers of the transition element MXene particles 10d, and Ti ions 41 play the role of combining layers 7d and 7d together. As a result, in the existing MXene particles 10c, water molecules 40 are easily intruded between layers 7c and 7c, and the presence of water molecules 40 leads to a decrease in electrical conductivity, that is, it is impossible to suppress the time-dependent deterioration of electrical conductivity caused by moisture absorption. In contrast, according to the transition element MXene particles 10d, as Figure 2As shown in (b), it is believed that inhibiting the intrusion of water molecules 40 into the interlayer can inhibit the time-dependent degradation of conductivity caused by moisture absorption, without significantly reducing the initial conductivity, and maintaining high conductivity. In addition, it is believed that the layer 7d containing the transition element MXene particles 10d is combined with the layer 7d by the transition element ions, which helps to ensure the strength of the MXene film. In addition, although it is only speculated, as mentioned above, under the interaction between the transition element ions and the MXene, the transfer of electrons is promoted, which is considered to be a factor in achieving high initial conductivity.
[0059] In addition, in the present invention, in order to verify the effect of the conductive film of the present invention, the reference MXene film used for comparison of hygroscopic resistance is in the following state: the preparation process of the MAX phase including the sintering process and the crushing process, the etching process, the delamination process, and the concentration process are the same as the manufacturing method of the conductive film of the present invention, and Li is contained in any form in the MXene film.
[0060] Also, in the above Figure 2 In the embodiment, the layers within a multilayer MXene (particle) are used as an example for explanation, but the so-called "between layers" of the transition element MXene particles in this embodiment is not limited to this, and for example, it also refers to between a single-layer MXene (particle) and other single-layer MXene (particles), and between a single-layer MXene (particle) and a multilayer MXene (particle).
[0061] In the conductive film of the embodiment, it is preferred that transition element ions exist between the layers constituting MXene, and the distance between the layers constituting MXene is shorter than that of a MXene film not containing the transition element. m X n In the case of Ti3 C2O2 (O-term) represented by Ti3 C2, the crystal structure is as follows Figure 3 As shown schematically in ( Figure 3 In the above example, 50 is a titanium atom, 51 is an oxygen atom, and other elements are omitted). Figure 3 The distance represented by the double arrow in . The above distance can be determined by the position of the low-angle peak below 11° (deg) corresponding to the (002) plane of MXene in the XRD line shape obtained by X-ray diffraction measurement. The higher the peak angle in the XRD line shape, the smaller the interlayer distance. The peak refers to the peak top. The X-ray diffraction measurement can be measured under the conditions shown in the embodiments described below. As the position of the above low-angle peak, for example, the range of 5 to 11° can be listed, among which, for example, above 6.2°, and further above 6.3° can be listed.
[0062] In addition, the conductive film of this embodiment, the M mX n Represented by Ti3C2, when the transition element is Ti, in the line shape obtained by X-ray diffraction measurement of the conductive film, there is a peak above 52° and below 58°, and a peak above 45° and below 49°, thereby being able to judge that in addition to Ti forming the skeleton of MXene, there is also Ti supported as a transition element.
[0063] The angle difference between the two peaks, i.e., the angle difference (unit: deg) obtained by (angle of the peak located at 52° to 58°) - (angle of the peak located at 45° to 49°), may be in the range of 7° to 10°.
[0064] In addition, in the present specification, the peaks of the XRD line shape, especially the peak located above 52° and below 58° and the peak located above 45° and below 49°, refer to the portion with a value higher than one measurement point before and after (in other words, having a positive extreme value) being regarded as the peak apex, and the height when a vertical line is drawn from the peak apex to the baseline being regarded as the peak height, and the peak height is more than 1 / 500 of the peak corresponding to the (002) plane.
[0065] The initial conductivity of the conductive film of the present embodiment can be obtained by measuring the thickness of the conductive film with a micrometer, or measuring it with a scanning electron microscope (SEM), or measuring it with a stylus surface profiler, and substituting the thickness of the conductive film and the surface resistivity of the conductive film measured by a four-probe method into the following formula to obtain an initial conductivity of 5000 S / cm or more.
[0066] Conductivity [S / cm] = 1 / (thickness of conductive film [cm] × surface resistivity of conductive film [Ω / □])
[0067] Whether the thickness of the conductive film is measured by a micrometer, a scanning electron microscope, or a stylus-type surface profiler depends on the thickness of the conductive film. As a standard for the measurement method, the measurement with the micrometer can be used when the thickness of the conductive film is thin. It can also be used when the thickness of the conductive film is 5 μm or more. The measurement with the stylus-type surface profiler can be used when the thickness of the conductive film is 400 μm or less, and the measurement with the scanning electron microscope can be used when the thickness of the conductive film is 200 μm or less, and when the above-mentioned stylus-type surface profiler cannot be used for measurement. When measuring with the scanning electron microscope, the measurement magnification can be determined according to the film thickness. When measuring with a stylus-type surface profiler, the Dektak (registered trademark) measuring instrument of Veeco Instruments Inc. is used for measurement. The thickness of the conductive film is calculated as an average value.
[0068] Excellent stability of conductivity means, as shown in the examples described below, that the conductivity after being exposed to an environment of a temperature of 25° C. and a humidity of 99% for 4 weeks is 10% or more, preferably 20% or more of the initial conductivity.
[0069] The conductive film of this embodiment can be used in any suitable application, for example, in any application requiring maintenance of high conductivity (reducing the decrease in initial conductivity and preventing oxidation) such as electrodes in suitable electrical devices or electromagnetic shielding (EMI shielding).
[0070] The electrode is not particularly limited, and may be, for example, a capacitor electrode, a battery electrode, a biosignal sensing electrode, a sensor electrode, an antenna electrode, etc. By using the conductive film of this embodiment, a large-capacitance capacitor and battery, a low-impedance biosignal sensing electrode, a highly sensitive sensor and an antenna can be obtained even in a smaller volume (device occupied volume).
[0071] The capacitor may be an electrochemical capacitor. An electrochemical capacitor is a capacitor that utilizes the capacitance generated by the physical and chemical reaction between an electrode (electrode active material) and ions (electrolyte ions) in an electrolyte, and can be used as a device for storing electrical energy (electrical storage device). A battery is a chemical battery that can be repeatedly charged and discharged. For example, a battery may be a lithium-ion battery, a magnesium-ion battery, a lithium-sulfur battery, a sodium-ion battery, etc., but is not limited thereto.
[0072] The biological signal sensing electrode is an electrode used to obtain biological signals. The biological signal sensing electrode is, for example, an electrode used to measure EEG (electroencephalogram), ECG (electrocardiogram), EMG (electromyogram), EIT (electrical impedance tomography), but is not limited thereto.
[0073] The sensor electrode is an electrode used to detect a target substance, state, abnormality, etc. Examples of the sensor include, but are not limited to, a gas sensor, a biosensor (a chemical sensor using a molecular recognition mechanism of biological origin), and the like.
[0074] Antenna electrodes are electrodes used to radiate electromagnetic waves into space and / or receive electromagnetic waves in space.
[0075] (Embodiment 2: Method for producing a conductive film)
[0076] Hereinafter, a method for producing a conductive film according to an embodiment of the present invention will be described in detail, but the present invention is not limited to such an embodiment.
[0077] A method for manufacturing a conductive film (first manufacturing method) of this embodiment includes the following steps:
[0078] (a1) preparing a precursor film comprising particles of a layered material having one or more layers, wherein the layers comprise: m X n A layer body represented by (wherein, M is at least one metal of Groups 3, 4, 5, 6, and 7, X is a carbon atom, a nitrogen atom, or a combination thereof, n is 1 to 4, and m is greater than n and 5 or less); a modification or terminal T present on the surface of the layer body (T is at least one selected from the group consisting of a hydroxyl group, a fluorine atom, a chlorine atom, an oxygen atom, and a hydrogen atom); and
[0079] (b1) coating the precursor film with a solution containing, in a solvent, one or more transition elements selected from the group consisting of Ti, V, Cr, Zr, Nb, Mo, Hf, Ta, W and Y in ion form. This manufacturing method can manufacture a conductive film containing the above transition elements.
[0080] Another method for manufacturing a conductive film according to the present embodiment (second manufacturing method) includes the following steps:
[0081] (a2) Prepare the MAX phase, which is represented by the following formula: m AX n Represented by (wherein, M is at least one metal of Group 3, 4, 5, 6, 7, X is a carbon atom, a nitrogen atom or a combination thereof, A is at least one element of Group 12, 13, 14, 15, 16, n is 1 to 4, m is greater than n and 5 to 5);
[0082] (b2) performing an etching treatment using an etching solution to remove at least a portion of the A atoms from the MAX phase;
[0083] (c2) performing an intercalation treatment of monovalent metal ions, which includes a step of mixing the etched product obtained by the etching treatment with a metal compound containing a monovalent metal ion;
[0084] (d2) performing a transition element intercalation treatment, which comprises the step of mixing the intercalation product of the monovalent metal ion obtained by the intercalation treatment of the monovalent metal ion and a solution containing one or more transition elements selected from the group consisting of Ti, V, Cr, Zr, Nb, Mo, Hf, Ta, W and Y in the form of ions in a solvent; and
[0085] (e2) At least partially removing the solvent from the transition element intercalation product obtained through the transition element intercalation treatment to obtain a conductive film.
[0086] This production method can also produce a conductive film containing the above-mentioned transition element.
[0087] Hereinafter, each step of the first manufacturing method and the second manufacturing method will be described in detail. First, the first manufacturing method will be described.
[0088] [First Manufacturing Method]
[0089] Process (a1)
[0090] As a precursor film, a predetermined dry MXene film is prepared. The production of the precursor film is not limited, and for example, when a slurry containing MXene (particles) in a liquid medium is used and the precursor film is obtained by spraying, it can be produced by the following method.
[0091] First, particles of a predetermined layered material (MXene particles) are prepared. Such MXene particles can be synthesized by selectively etching (removing and layer-separating as needed) A atoms (and as needed a portion of M atoms) from the MAX phase. The MAX phase is represented by the following formula: m AX n =(wherein, M, X, n and m are as described above, A is at least one element of Groups 12, 13, 14, 15 and 16, usually an element of Group A, representatively an element of Group IIIA and Group IVA, more specifically, may include at least one selected from the group consisting of Al, Ga, In, Tl, Si, Ge, Sn, Pb, P, As, S and Cd, preferably Al), and a layer consisting of A atoms is located between M m X n The MAX phase typically has a crystal structure between two layers (which may have a lattice in which each X is located in an octahedral array of M) when m=n+1, wherein a layer of X atoms is arranged one layer between each layer of n+1 layers of M atoms (these are collectively referred to as "M m X n In the embodiment of the present invention, a layer of A atoms (“layer of A atoms”) is arranged as a layer next to the layer of the n+1th M atoms, but the present invention is not limited to this.
[0092] The MAX phase is produced by a known method. For example, TiC powder, Ti powder and Al powder are mixed in a ball mill, and the obtained mixed powder is sintered in an Ar atmosphere to obtain a sintered body (massive MAX phase). Thereafter, the obtained sintered body is crushed with an end mill to obtain a powdered MAX phase for the next step.
[0093] By selectively etching (removing and layer-separating as needed) the A atoms (and as needed a part of the M atoms) from the MAX phase, the A atom layer (and as needed a part of the M atoms) is removed, and the hydroxyl groups, fluorine atoms, chlorine atoms, oxygen atoms, hydrogen atoms, etc. present in the etching solution (usually, an aqueous solution containing fluorine acid is used, but not limited thereto) are removed from the exposed M atoms.m X n The surface of the layer is modified and this surface is used as the end.
[0094] The above etching can be performed using F-containing - The etching solution may be implemented, for example, by a method using a mixture of lithium fluoride and hydrochloric acid, or by a method using hydrofluoric acid. The etching solution may contain a metal compound containing a monovalent metal ion, as in step (b2) of the second manufacturing method described later, and an intercalation treatment of the monovalent metal ion may be performed simultaneously with the above-mentioned etching. In this case, the content of the metal compound containing a monovalent metal ion in the etching solution may be the same as in step (b2) of the second manufacturing method described later.
[0095] After the above etching, any suitable post-treatment (such as ultrasonic treatment, manual shaking or automatic shaker, etc.) can be appropriately used to promote the layer separation (stratification, separation of multilayer MXene into single-layer MXene) of MXene. For example, a monovalent metal ion intercalation treatment can be performed, which includes a process of mixing the etched product obtained by the etching treatment with a metal compound containing a monovalent metal ion under the same conditions as the step (c2) of the second manufacturing method described later. In addition, excessive shear force during ultrasonic treatment will destroy MXene. Therefore, if you want to obtain a two-dimensional MXene with a larger aspect ratio (preferably a single-layer MXene), it is preferred to apply a suitable shear force by manual shaking or an automatic shaker.
[0096] When the precursor film is obtained by spraying, first, a slurry S containing MXene (particles) in a liquid medium is prepared. The concentration of the layered material particles in the slurry S can be, for example, 5 mg / mL or more, but in particular, because it can solve the agglomeration / overlapping of the particles and separate the layers according to the circumstances, it can be above 30 mg / mL without causing nozzle clogging. The higher the concentration of the layered material particles in the slurry S, the more a film of desired thickness can be manufactured in a shorter time, which is suitable for industrial mass production. The upper limit of the particle concentration of the layered material can be appropriately selected, for example, it can be 200 mg / mL or less. The concentration of the particles of the layered material can be understood as the solid component concentration in the slurry S, and the solid component concentration can be measured, for example, using a heating and drying weight measurement method, a freeze-drying weight measurement method, a filtration weight measurement method, and the like.
[0097] The slurry S may be a dispersion and / or suspension of particles 10a and / or 10b of a layered material contained in a liquid medium. The liquid medium may be an aqueous medium and / or an organic medium, preferably an aqueous medium. A representative aqueous medium is water, and depending on the circumstances, in addition to water, other liquid substances may also be contained in a smaller amount (for example, 30% by mass or less, preferably 20% by mass or less, based on the overall standard of the aqueous medium). The organic medium may be, for example, N-methylpyrrolidone, N-methylformamide, N,N-dimethylformamide, ethanol, methanol, dimethyl sulfoxide, ethylene glycol, acetic acid, and the like.
[0098] The precursor film can be produced by spraying the slurry S prepared in this way as described below. The precursor film may contain a liquid component derived from the liquid medium of the slurry S, or may not contain a liquid component substantially. The precursor film may not contain a so-called binder.
[0099] Reference Figure 4 , describing a method of separately ejecting a slurry (fluid) containing layered material particles in a liquid medium and a gas (other fluid) from a nozzle 20, causing them to collide (mix) with each other outside the nozzle 20, and causing the layered material particles to accumulate on a substrate 31 to form a precursor film 30.
[0100] More specifically, the nozzle 20 that can be used in the present embodiment is a nozzle called an external mixing multi-fluid nozzle. Figure 5 An example of an external mixing multi-fluid nozzle is shown in . As shown in this example, the nozzle 20 preferably has a structure in which the slurry and the gas collide with each other outside the nozzle 20 by means of a vortex flow.
[0101] Reference Figure 5The external mixing multi-fluid nozzle 20c is an external mixing vortex multi-fluid nozzle, which has a structure for causing the slurry S to collide with the gas G in a vortex outside the nozzle 20c. In more detail, the external mixing multi-fluid nozzle 20c has a head H, which is configured to eject the slurry S so that it collides with the gas G ejected as a vortex (preferably a high-speed rotating vortex) through other paths. For example, by using the nozzle 20c, a mist M containing layered material particles can be ejected from a mixed fluid of the slurry S and the gas G as follows. In the nozzle 20c, the gas G is ejected from the gas ejection port (not shown) through one or more spiral grooves (not shown) provided by a rotating member (not shown) assembled on the head H, and a high-speed rotating vortex of the gas G is generated. The slurry S is introduced into the fluid supply pipe provided inside the nozzle 20c for the slurry S under the negative pressure of the high-speed rotating vortex formed by the gas G, and is ejected from the fluid ejection port (not shown) at the front end of the fluid supply pipe. Then, in front of the head H of the nozzle 20c, the slurry S ejected from the fluid ejection port collides with the high-speed rotating vortex formed by the gas G ejected from the gas ejection port (the slurry is atomized). The mixed fluid (including the atomized slurry) formed in front of the head H is ejected from the nozzle 20c as a mist M containing layered material particles. Such an external mixing multi-fluid nozzle 20c may be an external mixing vortex multi-fluid nozzle (for example, Atomax Co., Ltd., Atomax nozzle) or the like.
[0102] In this way, the slurry S containing the layered material particles in the liquid medium and the gas G are ejected from the nozzle 20c separately by using the nozzle 20c, and they are made to collide with each other outside the nozzle 20c, so that the slurry S can be formed into a homogeneous mist M with extremely fine particles, and a strong shear force can be applied to the layered material particles. As a result, when the particles of the layered material are condensed, the condensation can be broken, and when the particles of the layered material overlap, the overlap can be disassembled. And / or, when the particles are particles with a multilayer structure, the layers can be separated (stratified).
[0103] The slurry S may be supplied to the nozzle 20c by either a pressurizing method or a suction method.
[0104] The gas G is not particularly limited, and may be, for example, air, nitrogen, etc. The pressure of the gas G can be appropriately set, and may be, for example, 0.05 to 1.0 MPa (gauge pressure).
[0105] The particle diameter of the mist M can be appropriately adjusted, and can be, for example, 1 μm or more and 15 μm or less.
[0106] The mist M sprayed from the nozzle 20 is supplied (coated) onto the surface of the substrate 31 (sprayed), and the particles of the layered material are deposited on the substrate 31 to form the precursor film 30. The liquid component (liquid medium from the slurry S) contained in the mist M can be at least partially removed, preferably completely removed, by drying during and / or after being supplied to the substrate 31.
[0107] The substrate is not particularly limited and can be made of any appropriate material. The substrate may be, for example, a resin film, a metal foil, a printed circuit board, a mounted electronic component, a metal pin, a metal wiring, a metal wire, or the like.
[0108] Drying can be carried out under mild conditions such as natural drying (typically at room temperature and pressure in an air atmosphere) or air drying (spraying air), or under more intense conditions such as warm air drying (spraying heated air), heat drying, and / or vacuum drying.
[0109] The spraying and drying from the nozzle 20 can be appropriately repeated until the desired film thickness is obtained. For example, the combination of spraying and drying can be repeatedly performed multiple times. However, according to the present embodiment, since a slurry containing MXene particles 10a and / or 10b at a higher concentration can be used, a thicker film (e.g., a thickness of 0.5 μm or more) can be obtained by only performing one spraying (and drying as appropriate), which can reduce the number of spraying (and drying as appropriate) performed to obtain the desired film thickness.
[0110] Thus, a precursor film can be manufactured as the precursor film 30. The precursor film 30 includes the particles 10a and / or 10b of the layered material, and may contain a liquid component from the liquid medium of the slurry S, or may not contain a liquid component substantially. The precursor film 30 does not contain a so-called binder.
[0111] In addition to the above-mentioned preparation of the precursor film by spraying, the precursor film can also be prepared by suction filtering the above-mentioned slurry or the supernatant containing MXene particles obtained by the above-mentioned stratification. In addition, the precursor film formed by spraying can also be prepared using a nozzle other than an external mixing multi-fluid nozzle.
[0112] Process (b1)
[0113] A solution is coated on the precursor film, wherein the solution contains one or more transition elements selected from the group consisting of Ti, V, Cr, Zr, Nb, Mo, Hf, Ta, W and Y in the form of ions in a solvent.
[0114] As the preparation of a solution containing the transition element as an ion in a solvent, a compound containing the transition element can be used. As the compound, for example, it is preferred to use one or more inorganic acid salts selected from the group consisting of sulfates, nitrates, acetates and phosphates of the transition element. More preferably, it is one or more inorganic acid salts among sulfates and acetates. The concentration of the compound contained in the solution is not particularly limited, for example, it can be in the range of 0.001M or more and 0.1M or less. When the sulfate is used, the concentration of the compound contained in the solution is preferably in the range of 0.001M or more and 0.1M or less. When the acetate is used, the concentration of the compound contained in the solution is preferably in the range of 0.01M or more and 0.1M or less. As a counter anion source, the inorganic acid salt can be cited, but it does not necessarily have to be an acid. As the solvent, water (for example, distilled water, purified water such as deionized water, etc.), lower alcohols with carbon numbers of about 2 to 4 (for example, ethanol, isopropanol, butanol, etc.), hexane, acetone and other organic solvents can be used, preferably water.
[0115] The coating includes, for example, commonly used coating methods such as dipping, brushing, roller, roller coater, air spraying, airless spraying, curtain coating, roller curtain coating, slot coating, and electrostatic coating.
[0116] The steps after coating are not particularly limited, and for example, the immersed coated article may be lifted out of the solution, washed with water, and then dried, for example, at 70 to 90°C for 1 to 2 hours and then at 120 to 160°C.
[0117] [Second Manufacturing Method]
[0118] Process (a2)
[0119] First, a MAX phase is obtained in the same manner as in step (a1) of the first production method.
[0120] The MAX phase can be produced by a known method. For example, TiC powder, Ti powder and Al powder are mixed in a ball mill, and the mixed powder is sintered in an Ar atmosphere to obtain a sintered body (massive MAX phase). Thereafter, the sintered body is crushed with an end mill to obtain a powdered MAX phase for the next step.
[0121] Process (b2)
[0122] An etching treatment is performed using an etching solution to remove at least a portion of the A atoms from the MAX phase. The conditions for the etching treatment are not particularly limited, and known conditions can be used. For example, a F-containing -The etching solution may be used, for example, a method using a mixture of lithium fluoride and hydrochloric acid, or a method using hydrofluoric acid, etc. The etching solution may contain a metal compound containing a monovalent metal ion, and the intercalation treatment of the monovalent metal ion may be performed simultaneously with the above-mentioned etching instead of the following step (c2) or together with the following step (c2). In this case, the content of the metal compound containing the monovalent metal ion in the etching solution is preferably 0.001% by mass or more. The above content is more preferably 0.01% by mass or more, and further preferably 0.1% by mass or more. On the other hand, from the viewpoint of dispersibility in the solution, it is preferred that the content of the metal compound containing the monovalent metal ion in the etching solution is 10% by mass or less, and more preferably 1% by mass or less.
[0123] Process (c2)
[0124] The intercalation treatment of monovalent metal ions is carried out, which includes the process of mixing the etched product obtained by the etching treatment with a metal compound containing monovalent metal ions. As monovalent metal ions constituting the metal compound containing monovalent metal ions, alkali metal ions such as lithium ions, sodium ions and potassium ions, copper ions, silver ions, gold ions, etc. can be listed. As metal compounds containing the monovalent metal ions, ionic compounds in which the above-mentioned metal ions are combined with cations can be listed. For example, iodides, phosphates, sulfide salts containing sulfates, nitrates, acetates, and carboxylates of the above-mentioned metal ions. As the monovalent metal ion, lithium ions are preferred as described above, and as the metal compound containing the monovalent metal ion, metal compounds containing lithium ions are preferred, more preferably ionic compounds of lithium ions, and further preferably one or more of iodides, phosphates, and sulfide salts of lithium ions. If lithium ions are used as metal ions, water hydrated with lithium ions has the most negative dielectric constant, so it is considered easy to monolayer.
[0125] The content of the metal compound containing the monovalent metal ion in the intercalation treatment mixture of the monovalent metal ion is preferably 0.001% by mass or more. The above content is more preferably 0.01% by mass or more, and further preferably 0.1% by mass or more. On the other hand, from the perspective of dispersibility in the solution, the content of the metal compound containing the monovalent metal ion is preferably 10% by mass or less, and more preferably 1% by mass or less.
[0126] After the mixing, the mixture may be stirred or left to stand. Examples of the stirring method include a method using a stirring rod such as a stirrer, a method using a stirring blade, a method using a mixer, and a method using a centrifuge.
[0127] Process (d2)
[0128] The intercalation product of the monovalent metal ion obtained by the intercalation treatment of the monovalent metal ion is mixed with a solution containing one or more transition elements selected from the group consisting of Ti, V, Cr, Zr, Nb, Mo, Hf, Ta, W and Y in the form of ions in a solvent. The type and concentration of the compound of the transition element contained in the solution are as described in step (b1) of the first manufacturing method. After the above mixing, stirring may be performed or the mixture may be left to stand. As the stirring method, for example, a method using a stirring rod of a stirrer, a method using a stirring blade, a method using a mixer, and a method using a centrifugal device can be cited.
[0129] Process (e2)
[0130] The conductive film is obtained by at least partially removing the solvent from the transition element intercalation product obtained by the transition element intercalation treatment. The method for at least partially removing the solvent is not particularly limited, and examples thereof include filtration, heating, and reduced pressure distillation. For example, suction filtration can be performed on the supernatant or clay obtained after washing the transition element intercalation product with water. After filtration, vacuum drying can be performed at 80°C for 24 hours to prepare a conductive film. The filter for suction filtration can, for example, use a membrane filter (Merck Co., Ltd., Durapore, pore size 0.45μm).
[0131] The above is a detailed description of the conductive film and the method for manufacturing the same according to the embodiment of the present invention, but various modifications can be made. In addition, the conductive film of the present invention can also be manufactured by a method different from the manufacturing method of the above embodiment. In addition, it should be noted that the method for manufacturing the conductive film of the present invention is not limited to providing only the conductive film of the above embodiment.
[0132] Example
[0133] [Manufacturing of MXene films containing transition elements]
[0134] (Example 1)
[0135] In Example 1, a Ti ion-supported MXene film was prepared as a sample (conductive film).
[0136] (Formation of Precursor Film)
[0137] Preparation of slurry
[0138] As MAX particles, Ti3AlC2 particles were prepared by a known method. The Ti3AlC2 particles (powder) were added to 9 mol / L hydrochloric acid together with LiF (10 mL of 9 mol / L hydrochloric acid for every 1 g of Ti3AlC2 particles), and stirred at 35°C with a stirrer for 24 hours to obtain a solid-liquid mixture (suspension) containing solid components from the Ti3AlC2 particles.
[0139] The solid-liquid mixture (suspension) is washed with pure water and separated and removed by a centrifuge (the remaining sediment after the supernatant is removed is washed again), and the above operation is repeated about 10 times. Then, the mixture to which pure water is added to the sediment is stirred for 15 minutes with an automatic shaker, and thereafter, a centrifugal separation operation is performed for 5 minutes with a centrifuge to separate it into a supernatant and a sediment, and the supernatant is removed by centrifugal dehydration. Thus, pure water is added to the remaining sediment after the supernatant is removed for dilution to obtain a crude purified slurry.
[0140] The crude purified slurry can be understood as MXene particles, which may include single-layer MXene and multi-layer MXene that is not monolayered due to insufficient layer separation (stratification). In addition, it also includes impurities other than MXene particles (unreacted MAX particles, and crystals of by-products brought about by etched A atoms (such as crystals of AlF3), etc.).
[0141] The crude purified slurry obtained above was placed in a centrifuge tube and centrifuged at a relative centrifugal force (RCF) of 2600×g for 5 minutes using a centrifuge. The supernatant after centrifugation was recovered to obtain a purified slurry. The purified slurry can be understood as containing a large amount of monolayer MXene as MXene particles. The remaining sediment after removing the supernatant was not used thereafter.
[0142] The purified slurry obtained above was placed in a centrifuge tube and centrifuged at an RCF of 3500×g for 120 minutes using a centrifuge. The supernatant obtained by centrifugation was separated and removed. The separated supernatant was not used thereafter. A clay-like substance (clay) was obtained as the remaining sediment after the supernatant was removed. Thus, Ti3C2T s - Water dispersion clay. This MXene clay is mixed with pure water in appropriate amounts to prepare a MXene water dispersion having a MXene solid content concentration of 75 mg / mL.
[0143] Formation of precursor membrane by filtration
[0144] 10 mL of MXene aqueous dispersion (MXene solid content concentration 75 mg / mL) was diluted to 15 mg / mL with pure water to obtain a total of 50 mL of aqueous dispersion. Thereafter, 5 mL of aqueous dispersion with a MXene solid content concentration of 15 mg / mL was extracted with a syringe and suction filtered overnight. The above filtration used a membrane filter (pore size 0.45 μm, Durapore manufactured by Merck Co., Ltd.). The filtrate obtained by suction filtration was then dried in a vacuum oven at 80°C overnight to obtain a filtered MXene membrane as a precursor membrane.
[0145] Forming precursor film by spraying
[0146] In addition, as another precursor film (MXene film), a MXene spray film was prepared in the following manner. As an external mixing multi-fluid nozzle, an external mixing vortex multi-fluid (two-fluid) nozzle (manufactured by Atomax Co., Ltd., Atomax nozzle AM12 type) was used. The slurry prepared above (solid content concentration 84 mg / mL) was added to a plastic syringe and installed on a syringe pump (manufactured by YMC Co., Ltd., YSP-101). The extrusion speed of the syringe pump was set to 5.0 mL / min, and the ejection port of the plastic syringe was connected to the liquid (slurry) supply port of the external mixing multi-fluid nozzle. On the other hand, the gas supply port of the external mixing multi-fluid nozzle was connected to the compressed air supply source (compressed air pipeline in the factory) via a plastic hose, and the gas ejection pressure from the nozzle was adjusted to 0.45 MPa (gauge pressure).
[0147] Then, the above-mentioned MXene solid content concentration of 15 mg / mL water dispersion and gas (air) were sprayed from an external mixing multi-fluid nozzle onto the surface of a substrate composed of gold-coated glass (produced by Wakin Institute Co., Ltd.). After spraying, it was dried overnight in a vacuum oven at 80°C to obtain a sprayed MXene film as a precursor film.
[0148] (Immersion in solution containing transition elements)
[0149] Next, 0.0384 g of 25% aqueous solution of titanium (IV) sulfate (manufactured by Kishida Chemical Co., Ltd.) was measured and fixed to 20 mL with pure water to prepare a 0.002 M aqueous solution of titanium sulfate. The filtered MXene membrane and the sprayed MXene membrane prepared in the above manner were immersed in 20 mL of the prepared 0.002 M aqueous solution of titanium sulfate, respectively, and left at room temperature for 24 hours. After 24 hours, the filtered MXene membrane and the sprayed MXene membrane were taken out from the aqueous solution of titanium sulfate, left to dry for another 3 days at room temperature, and then dried in a vacuum oven at 80°C overnight to obtain the sample (conductive membrane) of Example 1.
[0150] (Example 2)
[0151] In Example 2, a Cr ion-supported MXene film was prepared as a sample (conductive film).
[0152] (Formation of Precursor Film)
[0153] In the formation of the precursor film by spraying in Example 1, a sprayed MXene film was obtained as a precursor film in the same manner as in Example 1 except that the spraying was performed on a substrate composed of a polyimide film (manufactured by DuPont Toray Industries, Inc.).
[0154] (Immersion in a solution containing transition elements)
[0155] Next, 1.146 g of chromium acetate (III) (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) was measured and fixed to 50 mL with pure water to prepare a 0.1 M chromium acetate aqueous solution. The sprayed MXene film prepared in the above manner was immersed in 50 mL of the prepared 0.1 M chromium acetate aqueous solution and left at room temperature for 24 hours. After 24 hours, the sprayed MXene film was taken out from the 0.1 M chromium acetate aqueous solution and left at room temperature for another 1 day to dry. Thereafter, it was dried in an 80°C atmospheric pressure oven for 1 hour, and then dried at 150°C for 30 minutes to obtain the sample (conductive film) of Example 2.
[0156] (Example 3)
[0157] In Example 3, a Y ion-supported MXene film was prepared as a sample (conductive film).
[0158] (Formation of Precursor Film)
[0159] In the spray coating of Example 1, a sprayed MXene film was obtained in the same manner as in Example 1 except that the spray was applied onto a substrate composed of a polyimide film (manufactured by DuPont Toray Industries, Inc.).
[0160] (Immersion in a solution containing transition elements)
[0161] Next, 1.691 g of yttrium (III) acetate tetrahydrate (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) was measured and fixed to 50 mL with pure water to prepare a 0.1 M yttrium acetate aqueous solution. The sprayed MXene film prepared in the above manner was immersed in 50 mL of the prepared 0.1 M yttrium acetate aqueous solution and left at room temperature for 24 hours. After 24 hours, the sprayed MXene film was taken out from the 0.1 M yttrium acetate aqueous solution and left at room temperature for another 1 day to dry. Thereafter, it was dried in an 80°C atmospheric pressure oven for 1 hour, and then dried at 150°C for 30 minutes to obtain the sample (conductive film) of Example 3.
[0162] In addition, in the above-mentioned Examples 1 to 3, the transition element ion-loaded MXene membrane is obtained by immersing the precursor membrane (MXene membrane) in an aqueous solution containing the transition element, but the method for manufacturing the transition element ion-loaded MXene membrane is not limited to this. The intercalation treated product of the monovalent metal ion can also be mixed with a solution containing the transition element ions to perform the transition element intercalation treatment, and then the solvent can be at least partially removed from the transition element intercalation treated product by, for example, filtration, to obtain the transition element ion-loaded membrane.
[0163] (Comparative Example 1)
[0164] In Comparative Example 1, an Al ion-supported MXene film was prepared as a sample.
[0165] First, as a precursor membrane, a filtered MXene membrane and a sprayed MXene membrane were obtained in the same manner as in Example 1.
[0166] Next, 0.0150 g of aluminum nitrate nonahydrate (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) was measured and dissolved in 20 mL of pure water to prepare a 0.002 M aluminum nitrate aqueous solution. The filtered MXene membrane and the sprayed MXene membrane prepared as described above were immersed in 20 mL of the prepared 0.002 M aluminum nitrate aqueous solution and left at room temperature for 24 hours. After 24 hours, the filtered MXene membrane and the sprayed MXene membrane were taken out from the aluminum nitrate aqueous solution, left to dry for another 3 days at room temperature, and then dried in a vacuum oven at 80°C overnight to obtain a sample of Comparative Example 1.
[0167] (Comparative Example 2)
[0168] In Comparative Example 2, a MXene film (precursor film) that does not support ions was prepared as a sample.
[0169] As the precursor membrane, a filtered MXene membrane and a sprayed MXene membrane were obtained in the same manner as in Example 1. In Comparative Example 2, the filtered MXene membrane and the sprayed MXene membrane were not immersed in a solution containing a transition element, and the filtered MXene membrane and the sprayed MXene membrane, i.e., the precursor membrane, were used as samples of Comparative Example 2. In the following evaluation, Comparative Example 2 is indicated as a control (Control).
[0170] [Evaluation of MXene films containing transition elements]
[0171] (Accelerated test and conductivity measurement)
[0172] Using the samples of Examples 1 to 3 and Comparative Examples 1 and 2, the initial conductivity was measured, and the stability of the conductivity was evaluated in the following manner.
[0173] First, the sample was kept in a state of being exposed to an environment at room temperature (about 25°C) and a humidity of 99%, and the conductivity was measured one day after the start of the maintenance. Thereafter, the conductivity was measured at intervals of one week from the start of the maintenance to the fifth week. The conductivity was measured at three locations including near the center of the film for one sample. In addition, a low-resistance conductivity meter (Loresta AX MCP-T370 manufactured by Mitsubishi Chemical Analytical Science Co., Ltd.) was used for the measurement of the conductivity. The thickness of the sample (dried film) was measured using a micrometer (MDH-25MB manufactured by Mitutoyo Co., Ltd.). The results showing the time-dependent changes in the conductivity of Examples 1, 2 and 5 and Comparative Examples 1 and 2 are shown in FIG. Figure 6 middle. Figure 6 The "conductivity change rate" on the vertical axis is expressed as the ratio (%) of the subsequent conductivity to the initial conductivity, with the initial conductivity as 100%. In addition, regarding the initial conductivity, Example 1 is 6044 S / cm, Example 2 is 13514 S / cm, Example 3 is 15707 S / cm, Comparative Example 1 is 6305 S / cm, and Comparative Example 2 is 4454 S / cm.
[0174] according to Figure 6 The result of the MXene film (precursor film) without loaded ions, that is, the result of Comparative Example 2 (control), is that the conductivity after 1 day is significantly lower than the initial conductivity, and the conductivity will still decrease thereafter, and the stability of the conductivity is significantly poor. In contrast, in Example 1, the initial conductivity is high. Although the conductivity decreases after 1 day, the decrease in conductivity is fully suppressed compared to the Comparative Example 2, and the conductivity is stable. In addition, Examples 2 and 3 are the same as Example 1, and the initial conductivity is also high. Although the conductivity decreases once, the decrease in conductivity is fully suppressed compared to the Comparative Example 2, and the conductivity is stable. The Cr ion-loaded MXene film of Example 2 and the Y ion-loaded MXene film of Example 3 are also the same as the Ti ion-loaded MXene film of Example 1. The layers of the MXene film are connected together, and it is difficult for water molecules to enter. Therefore, it is considered that the conductivity is stable as mentioned above.
[0175] On the other hand, in Comparative Example 1 in which Al ions other than the prescribed transition element were supported, the degree of decrease in conductivity from the initial conductivity to one day later was substantially the same as that of Example 1, but the amount of subsequent decrease in conductivity was large and the stability of conductivity was poor.
[0176] In addition, a sprayed MXene film (dried film) was separately prepared, and the above-mentioned change in conductivity over time was measured. The sprayed MXene film (dried film) was formed in the same manner as Example 2 except that a 0.01M chromium acetate aqueous solution or a 0.001M chromium acetate aqueous solution was used instead of the 0.1M chromium acetate aqueous solution used for immersion in the transition element-containing solution in Example 2. As a result, it was confirmed that even when the transition element concentration in the transition element-containing solution used for the production of the sprayed MXene film was changed, the same tendency as that of Example 2 was shown. In addition, a sprayed MXene film (dried film) was separately prepared, and the above-mentioned change in conductivity over time was measured. The sprayed MXene film (dried film) was formed in the same manner as Example 3 except that a 0.01M yttrium acetate aqueous solution or a 0.001M yttrium acetate aqueous solution was used instead of the 0.1M yttrium acetate aqueous solution used for immersion in the transition element-containing solution in Example 3. As a result, it was confirmed that the same tendency as in Example 3 was exhibited even when the transition element concentration in the transition element-containing solution used for producing the spray MXene film was changed.
[0177] (Strength evaluation)
[0178] Using the samples in Example 1 and Comparative Examples 1 and 2 in which the sprayed MXene film was formed on the surface of the substrate made of gold-plated glass (manufactured by Waki Laboratory Co., Ltd.), a tape peeling test was performed as follows to evaluate the film strength of the samples.
[0179] Based on the standard (IPC-TM-650), the tape peeling test was performed twice.
[0180] First, as the first tape peeling test, prepare 3M Brand 600 1 / 2-inch tape (manufactured by 3M), tear off the first circle of the rolled tape, and use the second circle for the test. Pull out more than 5 cm of tape and stick it on the sprayed MXene film as the first tape. Completely expel the air between the first tape and the sprayed MXene film to make them close. Tear off the first tape from the sprayed MXene film in a direction of about 90° and observe the state of the film. In addition, the time for sticking the tape is within 1 minute. The results show Figure 7 middle. Figure 7 The photographs were taken with the substrate after the above test and the attached material on the first adhesive tape peeled off facing upward. Figure 7 (a) is the result of Example 1, Figure 7 (b) is the result of Comparative Example 1, Figure 7 (c) is the result of Comparative Example 2.
[0181] In addition, as the second tape peeling test, a new tape was attached to the sprayed MXene film attached to the torn tape in the same way as above, and the film state was observed after it was torn off. The results are shown in Figure 8 In. Figure 8 In the photo, the upper substrate and Figure 7 The same substrate as below. Figure 8 In the lower part of the photograph, among the tapes divided into left and right, the left side shows the back side of the second tape (attached matter), and the right side shows the back side of the first tape (attached matter after the second tape peeling test). Figure 8 (a) is the result of Example 1, Figure 8 (b) is the result of Comparative Example 1, Figure 8 (c) is the result of Comparative Example 2.
[0182] According to the above Figure 7 As a result of (a), in Example 1, the sprayed MXene film peeled off from the gold substrate surface, but according to the results of the second tape peeling test Figure 8 (a) There is almost only the attached tape on the left side, and the sprayed MXene film is still attached to the original tape on the right side. In other words, no peeling or cohesive peeling occurred in the sprayed MXene film. This shows that the sprayed MXene film is strengthened by carrying Ti ions.
[0183] In contrast, in Comparative Example 1, the adhesion between the gold glass slide (substrate) and the sprayed MXene film was weak, and the gold ( Figure 7 In Comparative Example 1, in the first tape peeling test, cohesive peeling in the sprayed MXene film hardly occurred in Comparative Example 2 described below, but in the second tape peeling test, the MXene film was transferred to the second tape on the left, and cohesive peeling occurred.
[0184] In Comparative Example 2, the adhesion between the gold slide glass (substrate) and the sprayed MXene film, as well as the strength of the sprayed MXene film itself, were weak, so in the first tape peeling test, the substrate was peeled off (the gold substrate was confirmed), and part of the sprayed MXene film remained, and cohesive peeling also occurred. This shows that the existing MXene film has low strength.
[0185] (XRD measurement)
[0186] XRD measurements were performed on the sprayed MXene films (dried films) of Example 1 and Comparative Examples 1 and 2. More specifically, XRD measurements of the sprayed MXene films were performed under the following conditions to obtain a two-dimensional X-ray diffraction image (line shape) of the sprayed MXene films. As a result, it was shown as Fig. 9 , and magnified Fig. 9 The range of 2° to 9° Fig.10 , and magnified Fig. 9 The range of 35° to 55° Fig.11 .
[0187] In the two-dimensional X-ray diffraction image (line shape), the peak position of the (002) plane in the range of 6 to 10° represents the distance between the nanosheets of the MXene film (interlayer distance). It can be seen that the higher the angle of the peak, the smaller the interlayer distance of the MXene. Fig.10 In the MXene film loaded with Ti ions, a peak appears on the high-angle side compared to the precursor film without ion loading. That is, the nanosheets are connected by Ti ions, and it can be considered that the interlayer distance of MXene is reduced. In addition, in the case of the MXene film loaded with Al ions in Comparative Example 1, the connection between nanosheets is not as good as that of Ti, and it is considered that the interlayer distance of MXene is greater than that of Ti.
[0188] (XRD measurement conditions)
[0189] ·Using device: MiniFlex600 manufactured by Rigaku Co., Ltd.
[0190] ·condition
[0191] Light source: Cu tube ball
[0192] Characteristic X-rays:
[0193] Measuring range: 2 degrees to 65 degrees
[0194] Stepping: 5deg / min
[0195] Stride: 0.02deg
[0196] In addition, a sprayed MXene film (dried film) was also prepared separately and XRD measurement was performed. The sprayed MXene film (dried film) was formed in the same manner as in Example 1 except that a 0.01M titanium sulfate aqueous solution or a 0.1M titanium sulfate aqueous solution was used instead of the 0.002M titanium sulfate aqueous solution used for the impregnation into the transition element-containing solution in Example 1. The resulting two-dimensional X-ray diffraction image (line shape) is shown in Fig.12 In. According to Fig.12 It can be seen that the different concentrations of the transition element solution during manufacturing have little effect on the structure. Fig.12 The two-dimensional X-ray diffraction image (line shape) of the Ti ion-supported MXene film shown is consistent with the Fig. 9 The two-dimensional X-ray diffraction images (line shapes) of the Ti ion-loaded MXene films are almost the same.
[0197] (Immersion in pure water of Comparative Example 2)
[0198] When the sample of Comparative Example 2 was immersed in pure water, the sample dispersed and became ink-like. This is considered to be because there is no support between the MXene nanosheets in pure water.
[0199] The following conclusions can be drawn from the above results. That is, as shown in the results of Example 1, the reason why the conductivity remains constant under high humidity is that it is considered that the Ti ions enter the MXene nanosheets and act as a bridge between the two nanosheets. It has always been known that MXene is condensed by ions, which is believed to be caused by the connection effect of Ti between MXene nanosheets. In more detail, the MXene nanosheets are electrostatically connected by Ti ions. Therefore, if compared with the precursor film, it is difficult for the MXene nanosheets to expand and water to enter. The surface of the MXene nanosheet is said to be negatively charged, and it can also be considered that the Ti ions as cationic species are maintained between the MXene nanosheets under the interaction of electrostatics. However, the part where the Ti ions enter will cause a certain gap between the MXene nanosheets, so it is believed that water will be absorbed in an amount corresponding to this gap, which is manifested as a decrease in conductivity after the accelerated test. Although a certain amount of water absorption occurs, if Example 1 doped with Ti ions is compared with Comparative Examples 1 and 2 without Ti ions, it is believed that the conductivity is suppressed to a certain value under the inter-membrane retention effect of Ti ions. It is believed that the same effect can also be exerted in Cr ion-loaded MXene membranes and Y ion-loaded MXene membranes.
[0200] In contrast, in Comparative Example 1 in which Al ions are supported instead of Ti ions, Fig.10 As shown, compared with the precursor film, the peak appears at a higher angle side, but compared with the Ti ion-supported MXene film, the peak appears at a lower angle side. It can be seen that when Al ions are used, the nanosheets are connected together and narrowed, but not as good as the effect of Ti on the MXene nanosheet retention function. As a result, although it can be confirmed that Comparative Example 1 can also suppress the decrease in conductivity caused by moisture absorption and has film strength, the performance is poor compared with the Ti ion-supported MXene film. In Comparative Example 1, as a reason for not having the same degree of MXene nanosheet retention function effect as Ti, as mentioned above, it is believed that there is a tendency for MXene to interact with the d orbital of the metal, especially. That is, Ti, which has more electrons in the d orbital, has a stronger interaction with the π electrons of MXene compared to Al, and thus has a stronger retention force between MXene, so it is believed that it helps to improve hygroscopic resistance (stability of conductivity) and film strength, but Al cannot ensure a stronger retention force between MXene, so it is believed that it will result in poor hygroscopic resistance (stability of conductivity) and film strength.
[0201] In addition, in Comparative Example 2, which is a precursor film, a peak appears on the highest angle side. This indicates that metal ions are not intercalated between layers, but water molecules are intercalated, and the interlayers are expanded. As a result, in Comparative Example 2, the MXene nanosheet-holding function brought by the transition metal is not present, the conductivity is significantly reduced, and the film strength is also the weakest.
[0202] This application claims priority based on Japanese Patent Application No. 2021-003543, which is incorporated herein by reference.
[0203] Industrial Applicability
[0204] The conductive film of the present invention can be used for any appropriate purpose, for example, it can be used as an electrode and electromagnetic shield in an electrical device. As an electrode, it can be used as a large-capacity capacitor, a battery, a low-resistance biological signal sensing electrode, a high-sensitivity sensor, and an antenna. As an electromagnetic shield, it is particularly preferably used as a high-shielding EMI shield.
[0205] Explanation of symbols
[0206] 1a, 1b layer main body (M m X n layer)
[0207] 3a, 5a, 3b, 5b modification or terminal T
[0208] 7a, 7b, 7c, 7d MXene layers
[0209] 10a, 10b, 10c MXene particles
[0210] 10d MXene particles containing transition elements
[0211] 20 Nozzle
[0212] 20c External Mix Multi-Fluid Nozzle
[0213] 30 Precursor film (MXene film)
[0214] 31 Substrate
[0215] 40 Water molecules
[0216] 41 Ti ions
[0217] 50 Titanium atoms
[0218] 51 oxygen atom
[0219] S slurry
[0220] G Gas
[0221] M Fog
[0222] H Nozzle head
Claims
1. A conductive film comprising particles of a layered material having one or more layers, wherein: The layers include: By the following formula: M m X n The layer body represented by Wherein, M is at least one metal of Groups 3, 4, 5, 6, or 7, X is a carbon atom, a nitrogen atom, or a combination of carbon and nitrogen atoms, n is greater than or equal to 1 and less than or equal to 4, m is greater than n and less than 5; The modification or terminal T present on the surface of the main body of the layer, T is at least one selected from the group consisting of a hydroxyl group, a fluorine atom, a chlorine atom, an oxygen atom and a hydrogen atom, The conductive film contains one or more transition elements selected from the group consisting of Ti, V, Cr, Zr, Nb, Mo, Hf, Ta, W and Y, and the transition elements do not constitute the M m X n itself, and exists between the layers.
2. The conductive film according to claim 1, wherein The M m X n Represented by Ti3C2, the transition element is Ti, In the line shape obtained by performing X-ray diffraction measurement on the conductive film, there is a peak at 52° to 58°, and there is a peak at 45° to 49°.
3. The conductive film according to claim 1 or 2, wherein Used as an electrode or electromagnetic shield.
4. A method for producing a conductive film, wherein: include: (a1) Preparing a precursor film, the precursor film comprising particles of a layered material having one or more layers, the layers comprising: The following formula: M m X n The layer body represented by Wherein, M is at least one metal of Groups 3, 4, 5, 6, or 7, X is a carbon atom, a nitrogen atom, or a combination of carbon and nitrogen atoms, n is greater than or equal to 1 and less than or equal to 4, m is greater than n and less than 5; The modification or terminal T present on the surface of the main body of the layer, T is at least one selected from the group consisting of a hydroxyl group, a fluorine atom, a chlorine atom, an oxygen atom and a hydrogen atom; and (b1) applying a solution on the precursor film, wherein the solution contains, as ions in a solvent, one or more transition elements selected from the group consisting of Ti, V, Cr, Zr, Nb, Mo, Hf, Ta, W and Y, wherein the transition elements do not constitute the M m X n itself.
5. A method for producing a conductive film, wherein: include: (a2) preparing a MAX phase, wherein the MAX phase is represented by the following formula: m AX n express, Wherein, M is at least one metal of Groups 3, 4, 5, 6, or 7, X is a carbon atom, a nitrogen atom, or a combination of carbon and nitrogen atoms, A is at least one element of Group 12, 13, 14, 15, or 16, n is greater than or equal to 1 and less than or equal to 4, m is greater than n and less than 5; (b2) performing an etching process using an etching solution to remove at least a portion of the A atoms from the MAX phase; (c2) performing an intercalation treatment of monovalent metal ions, which includes the step of mixing the etched product obtained by the etching treatment with a metal compound containing the monovalent metal ions; (d2) performing a transition element intercalation treatment, which comprises the step of mixing the monovalent metal ion intercalation product obtained by the monovalent metal ion intercalation treatment and a solution containing one or more transition elements selected from the group consisting of Ti, V, Cr, Zr, Nb, Mo, Hf, Ta, W and Y as ions in a solvent, wherein the transition element does not constitute the M m AX n itself; and (e2) At least partially removing the solvent from the transition element intercalation product obtained through the transition element intercalation treatment to obtain a conductive film.
Citation Information
Patent Citations
Disposable dust-proof mask
JP2021003543A
Physical forms of MXene materials exhibiting novel electrical and optical characteristics
CN107001051A
Two-dimensional metal carbide, nitride, and carbonitride films and composites for EMI shielding
CN109417863A